2013
DOI: 10.1242/dev.101725
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 79 identifies a novel population of migratory epithelial cells that initiates hair canal morphogenesis and regeneration

Abstract: The formation of epithelial tubes underlies the development of diverse organs. In the skin, hair follicles resemble tube-like structures with lumens that are generated through poorly understood cellular rearrangements. Here, we show that creation of the hair follicle lumen is mediated by early outward movement of keratinocytes from within the cores of developing hair buds. These migratory keratinocytes express keratin 79 (K79) and stream out of the hair germ and into the epidermis prior to lumen formation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 55 publications
4
81
2
Order By: Relevance
“…4F). Consistent with these findings, previous studies have indicated that mobilized bulge cells can be retained in the HF infundibulum, 15,36 and that HF isthmus-derived cells appear to migrate farther into the wound than do lower bulgederived cells. 10 It is important to note that these observations might also be explained if bulge-derived cells exhibit innate differences in proliferation or migration rates that delay their entry into the site of injury.…”
Section: Discussionsupporting
confidence: 77%
“…4F). Consistent with these findings, previous studies have indicated that mobilized bulge cells can be retained in the HF infundibulum, 15,36 and that HF isthmus-derived cells appear to migrate farther into the wound than do lower bulgederived cells. 10 It is important to note that these observations might also be explained if bulge-derived cells exhibit innate differences in proliferation or migration rates that delay their entry into the site of injury.…”
Section: Discussionsupporting
confidence: 77%
“…We have recently reported that mice expressing Hes1 promoter-driven Cre ERT2 display recombinase activity in suprabasal cells of the IFE and infundibulum (Veniaminova et al, 2013). By coupling this recombinase with an inducible ROSA26R promoter-driven YFP reporter allele, we also observed Cre activity in inner bulge and, less frequently, in outer bulge stem cells (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Under homeostatic conditions, these cells renew the hair follicle infundibulum independently of bulge stem cells, since bulge cells largely do not contribute to the infundibulum, while Lrig1+ stem cells do not contribute to the bulge or anagen follicle (Page et al, 2013; Veniaminova et al, 2013). In mice expressing Lrig1 promoter-driven Cre ERT2 and Ptch1 floxed alleles ( Lrig1;Ptch1 ), we observed numerous tumors associated with the isthmus and infundibulum 5 weeks after tamoxifen induction (Figure 1F).…”
Section: Resultsmentioning
confidence: 99%
“…We calculated a correlation network for expression of the type II keratin Krt79 (Figure 2g), which is expressed in cells that line the infundibulum and co-localizes in part with expression of Krt17 (Veniaminova et al, 2013). The expression network for Krt79 included, in addition to Krt17 , the stem cell marker Leucine-rich repeats and immunoglobulin-like domains 1 ( Lrig1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The expression network for Krt79 included, in addition to Krt17 , the stem cell marker Leucine-rich repeats and immunoglobulin-like domains 1 ( Lrig1 ). Importantly, Lrig1 is a transmembrane protein and a marker of a stem cell that maintains the infundibulum and sebaceous gland, but not the hair follicle nor the interfollicular epidermis (Page et al, 2013; Veniaminova et al, 2013). Immunohistochemical analysis confirmed that Krt79 and Lrig1 protein are both localized within the infundibulum region, but primarily in adjacent cells rather than in exactly the same cell population (Figure 2h).…”
Section: Resultsmentioning
confidence: 99%